Genetic analysis of a diallel cross in tomato cultivars. I. Yield - related characters - Maluf, Wilson Roberto; Miranda, João Eustáquio Cabral de; Campos, Joenes Pelúzio de (Pesquisa Agropecuaria Brasileira, 2014)
Jinks-Hayman genetic analysis was performed on yield-related characters of tomato (Lycopersicon esculentum Mill) in a diallel cross of six cultivars - Kada, Santo Antônio, São Sebastião, Ângela, Floradel e BGH 3470. These six cultivars and their fifteen possible F1 hybrids (no distinction was made between reciprocal crosses) were tested in 1977 in two locations - Viçosa (MG) and Ponte Nova (MG). No evidence of either epistasis or overdominance was found for any of the characters studied. Degree of dominance estimates showed the existence of complete dominance for increased total and marketable yield, incomplete dominance for higher number of fruit, higher number of marketable fruit, and lower percent fruit cracking; and absence of dominance for average weight of marketable fruit and percent early yield. The four bilocular cultivars of the Santa Cruz group (Kada, Santo Antônio, São Sebastião and Ângela) are genetically similar to each other, as far as total and marketable yield, total number of fruit and total number of marketable fruit.
Keywords: Lycopersicon esculentum Mill.; breeding; gene action